Common whores, vertuous women, and loveing wives : free will Christian women in colonial Maryland - Meyers, Debra, 1956- (Religion in North America ;, 2003)
Religious conflicts had a pronounced effect on women and their families in early modern England, but our understanding of that impact is limited by the restrictions that prevented the open expression of religious beliefs in the post-Reformation years. More can be gleaned by shifting our focus to the New World, where gender relations and family formations were largely unhampered by the unsettling political and religious climate of England. In Maryland, English Arminian Catholics, Particular Baptists, Presbyterians, Puritans, Quakers, and Roman Catholics lived and worked together for most of the 17th century. By closely examining thousands of wills and other personal documents, as well as early Maryland's material culture, this transatlantic study depicts women's place in society and the ways religious values and social arrangements shaped their lives. Common Whores, Vertuous Women, and Loveing Wives takes a revisionist approach to the study of women and religion in colonial Maryland and adds considerably to our understanding of the social and cultural importance of religion in early America.